2019
DOI: 10.1016/j.jdcr.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Erythromelanosis follicularis faciei et colli: Dermoscopy and dermatopathology correlates

Abstract: A 17-year-old Moroccan boy, without medical history or similar cases in the family, presented with a 3-year history of nonitchy erythemato-pigmented patches, surmounted by follicular papules, on both cheeks, without lesions of keratosis pilaris on the body (Fig 1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
4
10
0
Order By: Relevance
“…Errichetti et al for the first time and our findings were consistent with their study [6]. Mouni et al [7] later on revealed similar findings in their patients. Similar dermoscopic findings can be seen in erythrosis pigmentosa peribuccalis which is considered to be a variant of this disease by few authors [8].…”
Section: The Dermoscopic Finding Of Effc Was Reported Bysupporting
confidence: 92%
See 1 more Smart Citation
“…Errichetti et al for the first time and our findings were consistent with their study [6]. Mouni et al [7] later on revealed similar findings in their patients. Similar dermoscopic findings can be seen in erythrosis pigmentosa peribuccalis which is considered to be a variant of this disease by few authors [8].…”
Section: The Dermoscopic Finding Of Effc Was Reported Bysupporting
confidence: 92%
“…The findings on dermoscopy of follicular plugging, scaling, and reddish brown background correspond to histopathological findings of hyperkeratotic hair follicles, orthokeratosis, and ectatic vessels respectively. Gray-blue dots and granules correlate with the presence of pigmentary incontinence and dermal melanophages in the upper dermis respectively [6,7].…”
Section: The Dermoscopic Finding Of Effc Was Reported Bymentioning
confidence: 99%
“…On dermoscopy, EFFC presents with white scaling, follicular plugging, and several grey-blue dots interspersed over an erythematous-brown background. 26,27 This corresponds to orthokeratosis, follicular hyperkeratosis, pigment incontinence with dermal melanophages, and vasodilation on histology, respectively. 27 The grey-blue granules, as described by Errichetti et al and Maouni et al, are "peppered" around and inbetween follicular openings.…”
Section: Exogenous Ochronosismentioning
confidence: 99%
“…Dermoscopy of EFFC shows multiple round whitish areas with follicular plugs, some shows central hair, surrounded by blue gray spots or peppering in a reddish-brown background. [ 8 ] Dermoscopy of EPM includes follicular dilatation with yellowish keratotic plugs, perifollicular erythema, and scaling surrounded by slate-gray globules. [ 9 ] Histology of EFFC and EPM is similar and shows follicular hyperkeratosis, increased basal layer pigmentation, and incontinence of melanin pigment with dermal melanophages.…”
mentioning
confidence: 99%
“…Dermis shows perivascular and periadnexal lymphocytic infiltrate with vasodilatation. [ 8 ] EFFC has been found to be associated with keratosis pilaris of different body parts which postulated that EFFC is a variant of keratosis pilaris. [ 3 4 6 7 10 11 ] Juhlin et al .…”
mentioning
confidence: 99%